Corrosion resistant agent, method of making and use in cement
Patent Information
- Application Number
- CN202410547606.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-06
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-05-06
AI Technical Summary
但现有的耐腐蚀外加剂耐久性差,应用温度范围窄,无法满足大多数“三高气井”的固井要求,极大地阻碍了高酸性气田的勘探开发步伐
[0020] 1. In the preparation of a high-temperature-H2S coupled corrosion resistant cementitious slurry system, the corrosion resistant agent of this invention allows basic zinc carbonate to react with H2S to generate insoluble ZnS. The adhesion of ZnS to the surface of cement hydration products forms a corrosion-resistant protective layer, preventing H2S from penetrating into the cement stone and providing a certain degree of protection, thus improving the various properties of the cement stone after corrosion. Simultaneously, the in-situ growth of basic zinc carbonate in the pores of nano-clay hinders its dissolution in the cement slurry, slows down the formation of Zn(OH)2, and thus avoids the adverse effects of basic zinc carbonate on the rheological properties and thickening properties of the cement slurry. Furthermore, in addition to filling the pores of the cement stone and increasing the density of the cement matrix to inhibit H2S penetration, the nano-clay can also consume the cement hydration product calcium hydroxide through a pozzolanic reaction, thereby improving the corrosion resistance of the cement stone.
Smart Images

Figure CN118439809B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of oil and gas well cementing technology, specifically to a corrosion-resistant agent, its preparation method, and its application in cement. Background Technology
[0002] In H2S gas field environments, the downhole cement sheath is subjected to long-term corrosion by acidic gases, which will cause serious degradation of various properties of the cement sheath, causing it to lose its function of protecting the casing and sealing the formation. This will lead to problems such as gas channeling, formation fluid cross-contamination, and casing and drill string corrosion. In severe cases, it can lead to accidents such as the abandonment of oil and gas wells, posing a serious threat to the natural environment and personal safety, and increasing exploration and development costs.
[0003] Currently, the main method for resisting H2S corrosion is to add corrosion-resistant admixtures to form a protective layer against H2S on the cement stone surface. However, existing corrosion-resistant admixtures have poor durability and a narrow application temperature range, which cannot meet the cementing requirements of most "high-acidity, high-temperature, and high-volume gas wells," greatly hindering the exploration and development of high-acidity gas fields.
[0004] Therefore, the preparation of a high-temperature-H2S coupled corrosion cementing slurry system by combining corrosion-resistant additives and inorganic mineral materials has a simple production process and strong applicability, which has good market prospects and engineering demand. Summary of the Invention
[0005] Based on the above problems, the present invention provides a corrosion resistant agent, its preparation method and its application in cement, which can not only improve the H2S corrosion resistance of oil well cement stone, but also improve the degradation of the mechanical properties of cement stone under high temperature environment, and ensure the resistance of oil well cement stone to high temperature-H2S coupled corrosion.
[0006] To achieve the above-mentioned technical effects, the technical solution adopted by the present invention is as follows:
[0007] In a first aspect, the present invention discloses a corrosion resistant agent comprising basic zinc carbonate and a nano-clay carrier.
[0008] In a second aspect, the present invention discloses a method for preparing a corrosion resistant agent as described in the first aspect, comprising the following steps:
[0009] (1) Preparation of nano-clay carrier: Disperse nano-clay in deionized water to form nano-clay suspension, then add concentrated hydrochloric acid and sodium chloride, stir under water bath conditions, filter to obtain sample, wash with deionized water until the filtrate does not contain chloride ions, and dry in a freeze dryer to obtain nano-clay carrier.
[0010] (2) Preparation of corrosion resistant agent: The nano clay carrier is dispersed in deionized water to form a suspension; zinc acetate solution and anhydrous ethanol are gradually added to the suspension, and the mixture is ultrasonically dispersed and then carbamic acid solution is added. The mixture is stirred under water bath conditions, filtered to obtain the sample, and then washed with deionized water until the filtrate does not contain acetate ions. The corrosion resistant agent is obtained after drying and grinding in a freeze dryer.
[0011] In a preferred embodiment of the present invention, in step (1), the mixture is stirred at 500 rpm for 120 minutes in a 60°C water bath; in step (2), the mixture is stirred at 200 rpm for 180 minutes in a 90°C water bath.
[0012] In a preferred embodiment of the present invention, in step (2), the concentration of the zinc acetate solution is 1 mol / L and the concentration of the carbamic acid solution is 3 mol / L.
[0013] Furthermore, in step (2), the mass-to-volume ratio of the nano-clay carrier to the zinc acetate solution is 3:100, and the volume ratio of the zinc acetate solution, anhydrous ethanol, and carbamic acid solution is 100:53:100.
[0014] Thirdly, the present invention discloses the application of a corrosion resistant agent as described in the first aspect or a corrosion resistant agent prepared by the method described in the second aspect in the production and preparation of cementing slurry systems.
[0015] Fourthly, this invention discloses a high-temperature-H2S coupled corrosion resistant cementing slurry system, comprising the following raw materials in parts by weight: 50-55 parts of high sulfate-resistant high-temperature oil well cement, 15-20 parts of high-temperature stabilizer, 0.5-1 part of corrosion resistant agent, 0.5-1 part of retarder, 0.5-1 part of fluid loss reducer, 0.5-1 part of dispersant, and 21-33 parts of water, wherein the corrosion resistant agent is the corrosion resistant agent described in the first aspect or the corrosion resistant agent prepared by the method described in the second aspect.
[0016] In a preferred embodiment of the present invention, the high sulfate-resistant and high-temperature resistant oil well cement comprises the following minerals by mass fraction: C3S 40-45%, C2S 35%-40%, C3A 0-2%, and C4AF 13%-18%.
[0017] In a preferred embodiment of the present invention, the high-temperature stabilizer is selected from one or more of the following: quartz sand, red mud, microsilica, metakaolin, fly ash, and spodumene smelting slag.
[0018] In a preferred embodiment of the present invention, the retarder is tartaric acid, the water loss reducing agent is carboxymethyl cellulose, and the dispersant is a sulfonated aldehyde-ketone condensate.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. In the preparation of a high-temperature-H2S coupled corrosion resistant cementitious slurry system, the corrosion resistant agent of this invention allows basic zinc carbonate to react with H2S to generate insoluble ZnS. The adhesion of ZnS to the surface of cement hydration products forms a corrosion-resistant protective layer, preventing H2S from penetrating into the cement stone and providing a certain degree of protection, thus improving the various properties of the cement stone after corrosion. Simultaneously, the in-situ growth of basic zinc carbonate in the pores of nano-clay hinders its dissolution in the cement slurry, slows down the formation of Zn(OH)2, and thus avoids the adverse effects of basic zinc carbonate on the rheological properties and thickening properties of the cement slurry. Furthermore, in addition to filling the pores of the cement stone and increasing the density of the cement matrix to inhibit H2S penetration, the nano-clay can also consume the cement hydration product calcium hydroxide through a pozzolanic reaction, thereby improving the corrosion resistance of the cement stone.
[0021] 2. The high C2S mineral composition in the high sulfate-resistant and high-temperature oil well cement of this invention helps to reduce the calcium-silicon ratio of the cement hydration products, improve the high-temperature resistance of the hydration products, and reduce the calcium hydroxide content in the hydration products, thereby enhancing the acid corrosion resistance of the cement stone. Simultaneously, the high C4AF content in the mineral composition allows its hydration reaction to consume some calcium hydroxide, while the Al it provides... 3+ It can participate in the formation of C-(A)-SH, which can further improve the high temperature resistance of hydration products. Attached Figure Description
[0022] Figure 1 The XRD diffraction patterns of corrosion products before and after the addition of corrosion resistant agent provided by this invention.
[0023] Figure 2 SEM images of cement stone before and after the addition of corrosion resistant agent provided by this invention. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the embodiments and accompanying drawings. The illustrative embodiments and descriptions of the present invention are only used to explain the present invention and are not intended to limit the present invention.
[0025] Example 1
[0026] Preparation of corrosion resistant agents:
[0027] 30 parts by weight of nano-clay were dispersed in 600 parts of deionized water to form a nano-clay suspension. 10 parts of concentrated hydrochloric acid and 10 parts of sodium chloride were added evenly. The mixture was stirred at 500 rpm for 120 minutes in a 60°C water bath and filtered to obtain the sample. The sample was washed with deionized water until the filtrate was free of chloride ions and then dried in a freeze dryer to obtain the nano-clay carrier.
[0028] 3g of nano-clay carrier was dispersed in 80mL of deionized water to form a suspension. 100mL of 1mol / L zinc acetate solution and 53mL of anhydrous ethanol were gradually added to the suspension, and the mixture was ultrasonically dispersed for 15 minutes. 100mL of 3mol / L carbamic acid solution was added, and the mixture was stirred at 200rpm for 180 minutes in a 90℃ water bath. The sample was then filtered. The sample was washed with deionized water until the filtrate was free of acetate ions. After drying and grinding in a freeze dryer, the corrosion-resistant agent was obtained.
[0029] Example 2
[0030] Preparation of a high-temperature-resistant cementing slurry system resistant to H2S coupled corrosion:
[0031] Step 1: Prepare a cement slurry by mixing high sulfate-resistant high-temperature oil well cement (high sulfate-resistant high-temperature oil well cement includes the following mineral composition by mass fraction: C3S 40-45%, C2S 35%-40%, C3A 0-2%, C4AF 13%-18%), metakaolin, lithium slag, corrosion resistant agent prepared in Example 1, tartaric acid, carboxymethyl cellulose, sulfonated aldehyde ketone condensate, and water in a weight ratio of 53:9:6:0.5:0.5:1:1:29 according to the requirements of GB / T-19139 "Test Methods for Oil Well Cement").
[0032] Step 2: Place the cement slurry obtained in Step 1 into a cubic mold with dimensions of 50.8*50.8*50.8mm, and cure the prepared sample in a high-temperature and high-pressure curing autoclave at 90℃ and 20MPa for 3 days in accordance with GB / T-19139 "Test Methods for Cement in Oil Wells".
[0033] Step 3: After demolding the cement stone obtained in Step 2, core samples are taken using a drilling rig and then cylindrical samples with a length and diameter of 25 mm are obtained using a core cutter.
[0034] Step 4: Place a portion of the cement stone obtained in Step 3 into a high-temperature, high-pressure corrosion apparatus for H2S corrosion testing. The conditions are: H2S gas pressure 3 MPa, N2 gas pressure 7 MPa, and total pressure 10 MPa. To better simulate the humid conditions underground, a small amount of water is placed under the sample holder of the corrosion apparatus.
[0035] Step 5: Test the compressive strength and permeability of the cement stone obtained in Step 2 and Step 3 according to the method of GB / T-19139 "Test Methods for Cement in Oil Wells".
[0036] Example 3
[0037] Preparation of a high-temperature-resistant cementing slurry system resistant to H2S coupled corrosion:
[0038] Step 1: Prepare a cement slurry by mixing high sulfate-resistant high-temperature oil well cement (high sulfate-resistant high-temperature oil well cement includes the following mineral composition by mass fraction: C3S 40-45%, C2S 35%-40%, C3A 0-2%, C4AF 13%-18%), quartz sand, red mud, corrosion resistant agent prepared in Example 1, tartaric acid, carboxymethyl cellulose, sulfonated aldehyde ketone condensate, and water in a weight ratio of 54:15:5:0.8:0.6:0.9:0.7:23, according to the requirements of GB / T-19139 "Test Methods for Oil Well Cement".
[0039] Step 2: Place the cement slurry obtained in Step 1 into a cubic mold with dimensions of 50.8*50.8*50.8mm, and cure the prepared sample in a high-temperature and high-pressure curing autoclave at 90℃ and 20MPa for 3 days in accordance with GB / T-19139 "Test Methods for Cement in Oil Wells".
[0040] Step 3: After demolding the cement stone obtained in Step 2, core samples are taken using a drilling rig and then cylindrical samples with a length and diameter of 25 mm are obtained using a core cutter.
[0041] Step 4: Place a portion of the cement stone obtained in Step 3 into a high-temperature, high-pressure corrosion apparatus for H2S corrosion testing. The conditions are: H2S gas pressure 3 MPa, N2 gas pressure 7 MPa, and total pressure 10 MPa. To better simulate the humid conditions underground, a small amount of water is placed under the sample holder of the corrosion apparatus.
[0042] Step 5: Test the compressive strength and permeability of the cement stone obtained in Step 2 and Step 3 according to the method of GB / T-19139 "Test Methods for Cement in Oil Wells".
[0043] Example 4
[0044] Preparation of a high-temperature-resistant cementing slurry system resistant to H2S coupled corrosion:
[0045] Step 1: Prepare a cement slurry by mixing high sulfate-resistant high-temperature oil well cement (high sulfate-resistant high-temperature oil well cement includes the following mineral composition by mass fraction: C3S 40-45%, C2S 35%-40%, C3A 0-2%, C4AF 13%-18%), quartz sand, the corrosion resistant agent prepared in Example 1, tartaric acid, carboxymethyl cellulose, sulfonated aldehyde ketone condensate, and water in a weight percentage ratio of 53:19:1:0.5:0.8:0.7:25, according to the requirements of GB / T-19139 "Test Methods for Oil Well Cement".
[0046] Step 2: Place the cement slurry obtained in Step 1 into a cubic mold with dimensions of 50.8*50.8*50.8mm, and cure the prepared sample in a high-temperature and high-pressure curing autoclave at 90℃ and 20MPa for 3 days in accordance with GB / T-19139 "Test Methods for Cement in Oil Wells".
[0047] Step 3: After demolding the cement stone obtained in Step 2, core samples are taken using a drilling rig and then cylindrical samples with a length and diameter of 25 mm are obtained using a core cutter.
[0048] Step 4: Place a portion of the cement stone obtained in Step 3 into a high-temperature, high-pressure corrosion apparatus for H2S corrosion testing. The conditions are: H2S gas pressure 3 MPa, N2 gas pressure 7 MPa, and total pressure 10 MPa. To better simulate the humid conditions underground, a small amount of water is placed under the sample holder of the corrosion apparatus.
[0049] Step 5: Test the compressive strength and permeability of the cement stone obtained in Step 2 and Step 3 according to the method of GB / T-19139 "Test Methods for Cement in Oil Wells".
[0050] Comparative Example 1
[0051] Step 1: Prepare a cement slurry by mixing high sulfate-resistant high-temperature oil well cement (high sulfate-resistant high-temperature oil well cement includes the following mineral composition by mass fraction: C3S 40-45%, C2S 35%-40%, C3A 0-2%, C4AF 13%-18%), quartz sand, the corrosion resistant agent prepared in Example 1, tartaric acid, carboxymethyl cellulose, sulfonated aldehyde ketone condensate, and water in a weight ratio of 53:19:0:0.5:0.8:0.7:26 according to the requirements of GB / T-19139 "Test Methods for Oil Well Cement").
[0052] Step 2: Place the cement slurry obtained in Step 1 into a cubic mold with dimensions of 50.8*50.8*50.8mm, and cure the prepared sample in a high-temperature and high-pressure curing autoclave at 90℃ and 20MPa for 3 days in accordance with GB / T-19139 "Test Methods for Cement in Oil Wells".
[0053] Step 3: After demolding the cement stone obtained in Step 2, core samples are taken using a drilling rig and then cylindrical samples with a length and diameter of 25 mm are obtained using a core cutter.
[0054] Step 4: Place a portion of the cement stone obtained in Step 3 into a high-temperature, high-pressure corrosion apparatus for H2S corrosion. The experimental conditions are: H2S gas pressure 3 MPa, N2 gas pressure 7 MPa, and total pressure 10 MPa. To better simulate the humid conditions downhole, a small amount of water is placed under the sample holder of the corrosion apparatus.
[0055] Step 5: Test the compressive strength and permeability of the cement stone obtained in Step 2 and Step 3 according to the method of GB / T-19139 "Test Methods for Cement in Oil Wells".
[0056] Comparative Example 2
[0057] Step 1: G-grade oil well cement, quartz sand, corrosion resistant agent prepared in Example 1, tartaric acid, carboxymethyl cellulose, sulfonated aldehyde ketone condensate, and water are mixed in a weight ratio of 53:19:1:0.5:0.8:0.7:25 to prepare cement slurry according to the requirements of GB / T-19139 "Test Methods for Oil Well Cement".
[0058] Step 2: Place the cement slurry obtained in Step 1 into a cubic mold with dimensions of 50.8*50.8*50.8mm, and cure the prepared sample in a high-temperature and high-pressure curing autoclave at 90℃ and 20MPa for 3 days in accordance with GB / T-19139 "Test Methods for Cement in Oil Wells".
[0059] Step 3: After demolding the cement stone obtained in Step 2, core samples are taken using a drilling rig and then cylindrical samples with a length and diameter of 25 mm are obtained using a core cutter.
[0060] Step 4: Place a portion of the cement stone obtained in Step 3 into a high-temperature, high-pressure corrosion apparatus for H2S corrosion. The experimental conditions are: H2S gas pressure 3 MPa, N2 gas pressure 7 MPa, and total pressure 10 MPa. To better simulate the humid conditions downhole, a small amount of water is placed under the sample holder of the corrosion apparatus.
[0061] Step 5: Test the compressive strength and permeability of the cement stone obtained in Step 2 and Step 3 according to the method of GB / T-19139 "Test Methods for Cement in Oil Wells".
[0062] Comparative Example 3
[0063] Step 1: G-grade oil well cement, quartz sand, corrosion resistant agent prepared in Example 1, tartaric acid, carboxymethyl cellulose, sulfonated aldehyde ketone condensate, and water are mixed in a weight ratio of 53:19:0:0.5:0.8:0.7:26 to prepare cement slurry according to the requirements of GB / T-19139 "Test Methods for Oil Well Cement".
[0064] Step 2: Place the cement slurry obtained in Step 1 into a cubic mold with dimensions of 50.8*50.8*50.8mm, and cure the prepared sample in a high-temperature and high-pressure curing autoclave at 90℃ and 20MPa for 3 days in accordance with GB / T-19139 "Test Methods for Cement in Oil Wells".
[0065] Step 3: After demolding the cement stone obtained in Step 2, core samples are taken using a drilling rig and then cylindrical samples with a length and diameter of 25 mm are obtained using a core cutter.
[0066] Step 4: Place a portion of the cement stone obtained in Step 3 into a high-temperature, high-pressure corrosion apparatus for H2S corrosion. The experimental conditions are: H2S gas pressure 3 MPa, N2 gas pressure 7 MPa, and total pressure 10 MPa. To better simulate the humid conditions downhole, a small amount of water is placed under the sample holder of the corrosion apparatus.
[0067] Step 5: Test the compressive strength and permeability of the cement stone obtained in Step 2 and Step 3 according to the method of GB / T-19139 "Test Methods for Cement in Oil Wells".
[0068] Table 1 shows the mechanical properties of the samples prepared in Examples 2-4 and Comparative Examples 1-3 after curing in a high-temperature and high-pressure curing autoclave at 90℃ and 20MPa for 3 days and after H2S corrosion for 7 days. The addition of corrosion resistant agent does not have a significant impact on the mechanical properties of cement stone before corrosion. The difference between the examples and the comparative examples shows that both corrosion resistant agent and high sulfate-resistant high-temperature oil well cement can improve the H2S erosion resistance of cement stone.
[0069] Table 1. Mechanical Properties of Cement Stone
[0070]
[0071] Table 2 shows the permeability data of the samples prepared in Examples 2-4 and Comparative Examples 1-3 after curing in a high-temperature and high-pressure curing vessel at 90℃ and 20MPa for 3 days and after H2S corrosion for 7 days. The corrosion resistant agent and the high sulfate-resistant high-temperature oil well cement can reduce the permeability of cement stone, increase the density of cement stone, and thus hinder the penetration of H2S.
[0072] Table 2
[0073] The corrosion products of the corroded cement stone obtained in Example 4 and Comparative Example 1 were characterized by XRD, such as... Figure 1 As shown in the figure. The results indicate that the addition of corrosion inhibitors can effectively inhibit the transformation of hydration products into corrosion products gypsum and ettringite. At the same time, the diffraction characteristic peaks of ZnS can be detected, indicating that the presence of ZnS inhibits the penetration of H2S into cement stone.
[0074] The microstructure of the corrosion products of the corroded cement stone obtained in Example 4 and Comparison 1 was observed using SEM, such as... Figure 2 As shown in the figure. The results indicate that the presence of needle-like corrosion products, ettringite, was clearly observed in the comparative example, and the cement stone structure was damaged, with large gaps visible. In the example, no obvious corrosion products were observed, and the cement stone microstructure was relatively dense, indicating that the corrosion resistant agent can improve the cement stone's resistance to H2S corrosion.
[0075] This method utilizes basic zinc carbonate, nano-clay, and high-sulfate-resistant, high-temperature oil well cement as raw materials to design a high-temperature- and H2S-coupled corrosion-resistant cementing slurry system. From a scientific perspective, this method solves the problem of mechanical property degradation of cement stone under H2S and high-temperature environments. From a process perspective, it overcomes the complexity of traditional organic polymer corrosion-resistant agent preparation processes. This invention is of great significance for ensuring the efficient and safe exploitation of oil and gas wells in high-acidity gas reservoirs.
[0076] The above are embodiments of the present invention. The above embodiments and specific parameters are only for clearly illustrating the invention verification process and are not intended to limit the patent protection scope of the present invention. The patent protection scope of the present invention shall still be determined by its claims. Similarly, any equivalent structural changes made based on the description and drawings of the present invention shall also be included within the protection scope of the present invention.
Claims
1. A method for preparing a corrosion resistant agent, characterized in that, The corrosion resistant agent comprises basic zinc carbonate and nano-clay carrier, and the preparation method includes the following steps: (1) Preparation of nano-clay carrier: Disperse nano-clay in deionized water to form nano-clay suspension, then add concentrated hydrochloric acid and sodium chloride, stir under water bath conditions, filter to obtain sample, wash with deionized water until the filtrate does not contain chloride ions, and dry in freeze dryer to obtain nano-clay carrier. (2) Preparation of corrosion resistant agent: The nano clay carrier is dispersed in deionized water to form a suspension; zinc acetate solution and anhydrous ethanol are gradually added to the suspension, and the mixture is ultrasonically dispersed and then carbamic acid solution is added. The mixture is stirred under water bath conditions, filtered to obtain the sample, and then washed with deionized water until the filtrate does not contain acetate ions. The corrosion resistant agent is obtained after drying and grinding in a freeze dryer.
2. The preparation method according to claim 1, characterized in that: In step (1), the mixture is stirred at 500 rpm for 120 minutes in a 60°C water bath; in step (2), the mixture is stirred at 200 rpm for 180 minutes in a 90°C water bath.
3. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the zinc acetate solution is 1 mol / L and the concentration of the carbamic acid solution is 3 mol / L.
4. The preparation method according to claim 3, characterized in that: In step (2), the mass-to-volume ratio of the nano-clay carrier to the zinc acetate solution is 3g:100ml, and the volume ratio of the zinc acetate solution, anhydrous ethanol, and carbamic acid solution is 100:53:
100.
5. The application of the corrosion resistant agent prepared by the method according to any one of claims 1-4 in the production of cementing slurry systems.
6. A high-temperature-resistant cementing slurry system resistant to H2S coupled corrosion, characterized in that, The raw materials include the following parts by weight: 50-55 parts of high sulfate-resistant and high-temperature resistant oil well cement, 15-20 parts of high-temperature stabilizer, 0.5-1 part of corrosion resistant agent, 0.5-1 part of retarder, 0.5-1 part of fluid loss reducer, 0.5-1 part of dispersant, and 21-33 parts of water, wherein the corrosion resistant agent is a corrosion resistant agent prepared by the method described in any one of claims 1-4.
7. The high-temperature resistant H2S coupled corrosion cementing slurry system according to claim 6, characterized in that, The high sulfate-resistant and high-temperature resistant oil well cement comprises the following minerals by mass fraction: C3S 40-45%, C2S 35%-40%, C3A 0-2%, and C4AF 13%-18%.
8. The high-temperature resistant H2S coupled corrosion cementing slurry system according to claim 6, characterized in that, The high-temperature stabilizer is selected from one or more of the following: quartz sand, red mud, microsilica, metakaolin, fly ash, and spodumene smelting slag.
9. The high-temperature resistant H2S coupled corrosion cementing slurry system according to claim 6, characterized in that, The retarder is tartaric acid, the water loss reducer is carboxymethyl cellulose, and the dispersant is sulfonated aldehyde-ketone condensate.
Citation Information
Patent Citations
Preparation method of oil well cement additive for preventing hydrogen sulfide corrosion
CN104531110A
Oil well cement preservative, high-temperature cement paste in oil and gas well cementation and preparation method of high-temperature cement paste
CN117623663A